2015
DOI: 10.1038/cti.2015.15
|View full text |Cite
|
Sign up to set email alerts
|

Medical case reports in the age of genomic medicine

Abstract: The case report has been a pillar of medical literature but has been displaced recently because of inherent risks of bias. As we move towards precision medicine, however, the case report format could provide an important method for describing disease mechanisms based on rare genetic variants. Empirical evidence reveals that many previously unexplained Mendelian diseases are accounted for by rare heterozygous alleles, de novo mutations or compound heterozygous mutations, and that disease-associated variants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The low prevalence of rare diseases, the phenotype heterogeneity and the long latency period, may prevent and/or make the possibility of performing randomized clinical trials (RCTs) and large studies extremely difficult [1, 2]. Therefore, with these diseases, knowledge of treatment efficacy or any other type of clinical knowledge must be based only on observational studies, rare disease registries and case reports [2], where real world data and evidence play an important role in health care decisions [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low prevalence of rare diseases, the phenotype heterogeneity and the long latency period, may prevent and/or make the possibility of performing randomized clinical trials (RCTs) and large studies extremely difficult [1, 2]. Therefore, with these diseases, knowledge of treatment efficacy or any other type of clinical knowledge must be based only on observational studies, rare disease registries and case reports [2], where real world data and evidence play an important role in health care decisions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with these diseases, knowledge of treatment efficacy or any other type of clinical knowledge must be based only on observational studies, rare disease registries and case reports [2], where real world data and evidence play an important role in health care decisions [3]. However, RCTs are assessed, in evidence-based medicine as the best corroboration of the efficacy of new treatments, while case reports show a lower grade level of evidence [1].…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have underlined the impact of individual clinical reports' results in clinical practice and research [11,72]. Previous studies and guidelines have suggested the inclusion of case reports in systematic reviews, but they did not consider the exclusion of case reports a serious concern if there are other designs available with a higher grade of evidence than case reports [12,69].…”
Section: Discussionmentioning
confidence: 99%
“…It thus raises the issue of genetic counseling complexity for these incidental events not yet reported in publications and emphasizes the importance of multidisciplinary support. Literature should collect such data about these complex genetic events to create a medical bank [16,17], as described by Aronson, et al [18], to which refer to regarding the patient support, genetic counseling and medical monitoring of associated pathologies. In conclusion, our work describes for the first time the association of two genetic rearrangements affecting CDC73 gene.…”
Section: Discussionmentioning
confidence: 99%